Nonmalignant respiratory mortality and long-term exposure to PM10 and SO2: A 12-year cohort study in northern China. (December 2017) - Chen, Xi; Wang, Xue; Huang, Jia-ju; Zhang, Li-wen; Song, Feng-ju; Mao, Hong-jun; Chen, Ke-xin; Chen, Jie; Liu, Ya-min; Jiang, Guo-hong; Dong, Guang-hui; Bai, Zhi-peng; et al.
Graphical abstract: Highlights: The relationship between air pollution and respiratory disease is proposed. Nonmalignant respiratory disease mortality was associated with PM10 and SO2 . Passive smokers are susceptible to the harmful effects of air pollution.